The Relationship Between Strength Of Faith And Academic Resilience Mediated By Ihsan Goal Orientation And Self-Efficacy - Masruroh, Ani Wardatul; Purwanto, Edy; Sutoyo, Anwar (Universitas Negeri Semarang, 2023)
Academic resilience is significant for students, particularly vocational school students, because they are trained to become skilled and adaptive workers who are able to meet business/industry needs in accordance with developments in science, technology and art. If they do not have good academic resilience, they will lack courage, perseverance, rationality and insight. Based on these issues, the present study strived for investigating the relationship between the strength of faith and academic resilience mediated by ihsan goal orientation and self-efficacy. It used a correlational design and involved 278 grade eleven students. Based on the analysis, there found a positive relationship between strength of faith and ihsan goal orientation, self-efficacy, and academic resilience, ihsan goal orientation and self-efficacy were positively related to academic resilience, and lastly, ihsan goal orientation and self-efficacy had an indirect and positive relationship with strength of faith and academic resilience. Thus, counselors are advised to provide counseling services to enhance strength of faith, ihsan goal orientation, and self-efficacy to improve students’ resilience.